Records of king penguins at Stranger Point and Esperanza/Hope Bay, Antarctica - Juares, Mariana Alejandra; Rios, Ayelen; Albarrán, Katya Karla; Silvestro, Anahí Mariel; Perchivale, Pablo José; Casaux, Ricardo Jorge; Santos, Maria Mercedes (Polar Biology)
The king penguin (Aptenodytes patagonicus) is a subantarctic species, but breeders were recently reported in Antarctica. Stranger Point (South Shetland Islands) represents the southernmost breeding site recorded so far. Here, we report the observations of king penguins molting and attempting to breed at Stranger Point during 11 consecutive years, and the first record of a molting individual at Esperanza/Hope Bay (tip of the Antarctic Peninsula). From 2011/2012, breeding attempts occurred every year at Stranger Point, except in 2021/2022. Only during 2014/2015 and 2016/2017, a chick hatched and survived until 5 months and 1 month old, respectively. In the remaining seasons, the egg was abandoned before hatching. In mid-February 2018, a dead adult king penguin was found, and then only a female adult was observed there. Strikingly, during 2017/2018 and 2018/2019, a second egg was laid some days after the first egg was abandoned. Unfortunately, the pair was not able to establish itself at Stranger Point, and no further sightings of molting king penguins were recorded at Esperanza/Hope Bay since the 2018/2019 season. Notwithstanding this, our observations highlight the importance of reporting all records of king penguins in Antarctica, thus providing fundamental information to assess future climate-driven shifts in the bio-geographic range of this species and the status of the population. Fil: Juares, Mariana Alejandra. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Rios, Ayelen. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Albarrán, Katya Karla. No especifíca; Fil: Silvestro, Anahí Mariel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Centro de ...